Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus - Molineri, Carlos; Salles, Frederico F. (Zootaxa, 2017)
The type species of the genus Campsurus Eaton 1868, Campsurus latipennis (Walker 1853), is redescribed, and some historical problems about its identity are addressed; notably, specimens had been assigned to two different species almost since its description. The nymph of C. latipennis is described for the first time. The following species are redescribed and/or rediagnosed: C. cuyuniensis Traver 1947, C. essequibo Traver 1947, C. lucidus Needham & Murphy 1924, C. indivisus Ulmer 1942 (=C. duplicatus Spieth 1943 syn. nov., nymph described for the first time here), C. litaninensis Spieth 1943, and C. segnis Needham & Murphy 1924. Eleven new species of Campsurus are described and illustrated: C. salobra sp. nov. (based on male and female imagos), C. nessimiani sp. nov. (based on male imago and nymph), C. dasilvai sp. nov. (based on male imago), C. zunigae sp. nov. (=Campsurus sp. B Traver 1947; based on male imago and nymph), C. pereirae sp. nov. (based on male and female imagos), C. janae sp. nov. (based on male subimago), C. demeni sp. nov. (based on male imago), C. sinamari sp. nov. (based on male and female imagos), C. inusitatus sp. nov. (=Campsurus sp. D Traver 1947; based on male imago), C. cotaxe sp. nov. (based on male and female imagos), and C. povilla sp. nov. (based on male and female imagos, nymph). The unknown female adult of C. amapaensis Molineri & Emmerich 2010 is described for the first time. Campsurus vulturorum Emmerich & Molineri 2011 is reported from Brazil for the first time. A key to separate male imagos of species of Campsurus is provided.